1999
DOI: 10.1021/jf9809582
|View full text |Cite
|
Sign up to set email alerts
|

Direct Intestinal Absorption of Red Fruit Anthocyanins, Cyanidin-3-glucoside and Cyanidin-3,5-diglucoside, into Rats and Humans

Abstract: We determined red fruit anthocyanins, cyanidin-3-glucoside (Cy-g) and cyanidin-3,5-diglucoside (Cy-dg), incorporated into plasma and liver of rats and human plasma by UV-HPLC. Fifteen minutes after an oral supplementation of a mixture of 320 mg of Cy-g and 40 mg of Cy-dg/kg of body weight, rats showed an increase to a maximum of 1563 microg (3490 nmol) of Cy-g/L and 195 microg (320 nmol) of Cy-dg/L in plasma and 0.067 microg (0.15 nmol) of Cy-g/g and a trace of Cy-dg together with methylated metabolites such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
273
3
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(310 citation statements)
references
References 26 publications
(29 reference statements)
26
273
3
8
Order By: Relevance
“…On the other hand, delphinidin-3-rutinoside, cyanidin-3-rutinoside, delphinidin-3-glucoside, and cyanidin-3-glucoside from blackcurrant have been found directly absorbed into the human blood circulating system and their glycosylated forms are excreted into urine [69]. This observation is also supported by a previous study that after 30 minutes of consumption of anthocyanin mixture from red fruit, the absorbed anthocyanins were not metabolized into the aglycones or any other metabolite forms in the human body [70]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninssupporting
confidence: 62%
“…On the other hand, delphinidin-3-rutinoside, cyanidin-3-rutinoside, delphinidin-3-glucoside, and cyanidin-3-glucoside from blackcurrant have been found directly absorbed into the human blood circulating system and their glycosylated forms are excreted into urine [69]. This observation is also supported by a previous study that after 30 minutes of consumption of anthocyanin mixture from red fruit, the absorbed anthocyanins were not metabolized into the aglycones or any other metabolite forms in the human body [70]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninssupporting
confidence: 62%
“…rats administered BoAnt and a report describing the absorption of cyanidin 3-O-glucoside from the gastrointestinal tract (Tsuda et al, 1999a;Miyazawa et al, 1999) may support that at least a portion of BoAnt absorbed from the gastrointestinal tract acted antioxidatively. However, as the intestinal contents were a strong purple color, indicating the absorbability of BoAnt may be very low, and as the total content of cyanidin 3-O-diglucoside, cyanidin 3-O-glucosylrutinoside and cyanidin 3-O-glucoside in liver was very little (30-40 g/liver), it is necessary to determine precisely if the absorbed anthocyanins and/or their metabolite acted antioxidatively to suppress increase in TBARS in the liver homogenate by AAPH.…”
Section: Discussionmentioning
confidence: 94%
“…Katsube et al (2003) reported that cyanidin-3-glucoside inhibited the proliferation of HL60 human leukemia cells, but did not inhibit the proliferation of HCT-116 human colon carcinoma cells. The viability of HL-60 cells was reduced by about 50% with cyanidin-3-glucoside at 300 μg/mL and present in rat plasma (0.31 μmol/L), while Miyazawa et al (1999) reported the direct intestinal absorption of anthocyanins in the intact glycoside form, cyanidin-3-glucoside and cyanidin-3,5-diglucoside, into human bodies after oral supplementation, and that no aglycons or conjugates of anthocyanins occurred in human plasma (24 nmol of cyanidin-3-glucoside /L). On cellular uptake, Murota et al (2000) reported that quercetin, which is not a member of the anthocyanidin family, but is one of the flavonoids, passed through Caco-2 monolayers much more efficiently than quercetin glucosides.…”
Section: Discussionmentioning
confidence: 96%